Planning and evaluating library networked services and resources (Libraries Unlimited, 2004)
This collection of 11 essays follows the cables behind the scenes to help library professionals evaluate and select networked services and resources that best meet the need of patrons. Essay topics include planning, selecting evaluation approaches, assessing services and resources, choosing performance indicators, performing needs assessments, dealing with legal and business matters, developing policy, allocating resources, penetrating vendor usage statistics from both sides, and considering key issues and future directions (booknews.com)